Revisiting the Assumptions of Adult Learning - Trevor Cox; Ed Cunliff (Adult Education Research Conference, 2023)
This roundtable suggests expanding adult education principles would benefit practitioners and lessen generational divides created by the assumptions of “adult” education as a process distinct from learning in younger individuals.
Keywords: educational systems; generational equity; science of learning; andragogy